# 4s+18=3(s+8)

## Simple and best practice solution for 4s+18=3(s+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 4s+18=3(s+8) equation:

Simplifying
4s + 18 = 3(s + 8)
Reorder the terms:
18 + 4s = 3(s + 8)
Reorder the terms:
18 + 4s = 3(8 + s)
18 + 4s = (8 * 3 + s * 3)
18 + 4s = (24 + 3s)
Solving
18 + 4s = 24 + 3s
Solving for variable 's'.
Move all terms containing s to the left, all other terms to the right.
Add '-3s' to each side of the equation.
18 + 4s + -3s = 24 + 3s + -3s
Combine like terms: 4s + -3s = 1s
18 + 1s = 24 + 3s + -3s
Combine like terms: 3s + -3s = 0
18 + 1s = 24 + 0
18 + 1s = 24
Add '-18' to each side of the equation.
18 + -18 + 1s = 24 + -18
Combine like terms: 18 + -18 = 0
0 + 1s = 24 + -18
1s = 24 + -18
Combine like terms: 24 + -18 = 6
1s = 6
Divide each side by '1'.
s = 6
Simplifying
s = 6`